UN Food Systems Summit sustainable livestock coalition - CGIAR Research Program on Livestock (2021)
UN Food Systems Summit coalition on sustainable livestock created, with ILRI as partner, to enhance enabling environment for inclusion of livestock in food systems including animal source foods in diets